Migration and imperfect labor markets: theory and cross-country evidence from Denmark, Germany and the UK - Brücker, Herbert; Hauptmann, Andreas; Jahn, Elke J.; Upward, Richard (2013)
We investigate the labor market effects of immigration in Denmark, Germany and the UK, three countries which are characterized by considerable differences in labor market institutions and welfare states. Institutions such as collective bargaining, minimum wages, employment protection and unemployment benefits affect the way in which wages respond to labor supply shocks, and, hence, the labor market effects of immigration. We employ a wage-setting approach which assumes that wages decline with the unemployment rate, albeit imperfectly. We find that the wage and employment effects of immigration depend on wage flexibility and the composition of the labor supply shock. In Germany immigration involves only moderate wage, but large unemployment effects, since immigrants are concentrated in labor market segments with low wage flexibility. The reverse is true for the UK and Denmark.